The role of nursing in the face of sexual changes in the climacteric period (Research, Society and Development, 2022)
Objective: This study arose out of the need to assess knowledge about sexuality in menopause among nurses in the Family Health Strategy. Method: Field research, with a quantitative approach, descriptive and cross-sectional. Data collection was carried out from June to July 2015. Results: For the evaluation of the questionnaire, 13 professionals were consulted to evaluate the questionnaire that deals with human sexuality. Overall, only one of the experts considered the questionnaire to be reasonable. Thus, the questionnaire was approved by the experts' stage. Cronbach's alpha reliability coefficient was also applied, obtaining a result equal to 0.86. Which indicates its reliability in the experts' answers. Final considerations: There is a need for transversality of nursing care to women in menopause, from dealing with the care of the body with propriety and intimacy with it, its most elementary aspects of body hygiene care, to those technically more complex, such as identifying inadequacies and sexual dysfunctions prescribing nursing care.